Drivers of consumer acceptability of cassava gari-eba food products across cultural and environmental settings using the triadic comparison of technologies approach (tricot) - Olaosebikan, Olamide; Bello, Abolore; Sousa, Kauê de; Ndjouenkeu, Robert; Adesokan, Michael; Alamu, Emmanuel Oladeji; Agbona, Afolabi; Etten, Jacob van; Ngoualem Kégah, Franklin; Dufour, Dominique; Bouniol, Alexandre; Teeken, Béla (Wiley, 2024)
BACKGROUND Nigeria and Cameroon are multi-ethnic countries with diverse preferences for food characteristics. The present study aimed to inform cassava breeders on consumer-prioritized eba quality traits. Consumer testing was carried out using the triadic comparison of technologies (tricot). Diverse consumers in villages, towns and cities evaluated the overall acceptability of eba made from different cassava genotypes. Data from both countries were combined and linked to laboratory analyses of eba and the gari used to make it.